32.1: Invited Paper: An Inkjet Printed 31‐inch UHD AMOLED Display. (28th November 2018) - Wu, Yuan Chun; Wu, Tsungyuan; Iguchi, Shinsuke; Li, Xiang-Long; Zhou, Jiankai; Hao, Peng; Cai, Yuying; Tang, Jia; Zhou, Xing-Yu; Hsu, Yuan-Jun; Lu, Po-Yen
Abstract : An inkjet printed 31‐inch UHD AMOLED display has been successfully developed in this report. Special designed small size pixels, high thermal stable top‐gate self‐aligned a‐IGZO TFTs, multiple‐planarization method and cost‐efficient inkjet printing process make the display very attractive. For the AMOLED display, HIL, HTL and EML (Red, Green, Blue) layers were printed in multiple‐planarized small pixels by precisely controlling the ink droplets. And ETL, cathode were prepared on the whole panel by VTE with just common masks instead of complicated and expensive FMMs, which provides a low‐cost fabrication approach for the following emerging inkjet printing display era. The light‐on image of the developed display indicates that good full color and display uniformity has been successfully realized.